Disitamab Vedotin plus anti-PD-1 antibody show good efficacy in refractory primary urethral cancer with low HER2 expression: a case report - Zheng, Yue; Xue, Yin-Yin; Zhao, Ya-Qin; Chen, Ye; Li, Zhi-Ping (Frontiers in Immunology, 2023)
Primary urethral carcinoma (PUC) has a low incidence, but with high aggressiveness. Most of the patients are found in late stage, with poor prognosis. At present, chemotherapy is still the main treatment for metastatic PUC, but it has limited effect. Here, we report a case of metastatic PUC with low HER2 expression that developed disease progression after multiline therapy including chemotherapy, programmed death-1 (PD-1) inhibitors and multi-targeted receptor tyrosine kinase (RTK) inhibitor. After receiving Disitamab Vedotin(a novel antibody drug conjugate, ADC) and toripalimab (a PD-1 inhibitor), the patient achieved persistent PR, and the PFS exceeded 12 months up to now. Our report indicates that, despite the patient of metastatic PUC has low expression of HER2, it is still possible to benefit from Disitamab Vedotin combined with PD-1 inhibitor, which may reverse the drug resistance of PD-1 inhibitor and chemotherapy to a certain extent. But larger sample studies are needed to determine the efficacy of this treatment strategy and its impact on survival.